Clinical Efficacy of Probiotics as An Adjunct to Scaling and Root Planning in The Treatment Of Chronic Periodontitis - Sana Ikram; Muhammad Arsalan Raffat; Saeeda Baig; Shazia Akbar Ansari; Kevin Joseph Jerome Borges; Nuzhat Hassan (KARACHI MEDICAL AND DENTAL COLLEGE, 2019)
Objective: The objective of this study was to assess  the  clinical  efficacy  of  scaling  and  root  planing  (SRP) alone and SRP along with adjunctive probiotic containing Lactobacillus reuteri (L.reuteri) in the management of chronic periodontitis (CP) and comparing the efficacy of two treatment modalities. Methods: Twenty-eight systemically healthy participants, clinically diagnosed with CP on  the  bases  of  pocket depth were enrolled from the outpatient department of Periodontology, Ziauddin College of Den-     tistry, Ziauddin University, Clifton, Karachi, Pakistan. After complete periodontal examination all clinical periodontal parameter i.e.,  Probing  Pocket  depth  (PPD),  Clinical  attachment  level  (CAL),  percentage  sites for plaque accumulation (PI) and bleeding on probing (BOP)  were  measured  and  recorded  at  baseline, 6 weeks and 12 weeks after therapy. Patients meeting the inclusion criteria  underwent  non-  surgical periodontal therapy i.e. SRP both with  hand  instruments  and  with  ultrasonic  scalers. After  SRP oral hygiene measures were reassured and then participants were  randomly  allocated  to  one  of  two  groups i.e., Probiotics (N=14) or Placebo (N=14). Both L. reuteri and placebo were given twice daily for          12 weeks and patients were recalled for assessment. Results: At baseline both groups were similar clinically. Intra-group comparison of clinical periodontal parameters showed improvement in the participants of both  groups.  Inter-group  comparison  showed  greater reduction in PPD and BOP and more gain in CAL in probiotic group on each follow up visits and statistically significant difference was  observed  in  two  groups.  Whereas  for  PI  the  difference  between  two groups at follow-up visit was insignificant i.e. both treatment strategies were equal in reducing per-  centage sites of plaque accumulation. Conclusion: The results of our study concludes L.reuteri containing probiotic along with SRP is superior   when compared to SRP alone in terms of resolving inflammation and  improving  periodontal  health.  Probiotics can be used as a promising alternative adjunctive therapy with minimal or no side effects in           the treatment of chronic periodontitis.